Age-related changes in children’s threshold exposure duration for recognition of test objects - Serdiuchenko, V.I.; Zheliznik, M.B. (Ukrainian Journal of Ophthalmology, 2026)
Background: Timely detection of an object in the visual field is of primary importance to adults and children. Purpose: To investigate threshold exposure duration for recognition of test objects (TEDRTO) in normal vision children of various age groups. Materials and Methods: Four hundred and sixteen children (832 eyes; age, 5 to 17 years) with a refraction within the age norm (emmetropia or hyperopia of up to 1.0 D) were included into the study and underwent assessment of TEDRTO with a special electronic apparatus. The apparatus was used to expose a test object (an illuminated Landolt’s ring subtending 8 minutes of arc) against a black background. Results: In children of 5 to 6 years, 7 to 10 years, 11 to 14 years, and 15 to 16 years, binocular threshold exposure durations for recognition of the white test object subtending 8 minutes of arc were found to be 2.1 ± 1.3 ms, 1.4 ± 0.5 ms, 1.1 ± 0.3 ms and 1.1 ± 0.3 ms, respectively. Conclusions: The results obtained can be used as reference values while investigating threshold exposure durations for recognition of test objects in various disorders of the visual system.